2005
DOI: 10.1007/s10658-005-1225-9
|View full text |Cite
|
Sign up to set email alerts
|

Host Specialization not Detected Among Isolates of the EC-1 Lineage of Phytophthora infestans Attacking Wild and Cultivated Potatoes in Peru

Abstract: To determine whether populations of Phytophthora infestans attacking wild and cultivated potatoes in the highlands of Peru are specialized on their hosts of origin, we characterized isolates using several neutral markers, metalaxyl resistance and for aggressiveness in a detached leaf assay. One hundred and fifty-three isolates were collected from the northern and central highlands of Peru from different potato cultivars (both modern and native cultivars) and from different species of wild, tuber-bearing potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…More recently, in commercial varieties and selected clones from INIAP's national potato breeding programme, 27, 17 and 37 races were found in Carchi, Cotopaxi and Pichincha provinces, respectively (Tello, 2008). In Peru and Colombia three clonal lineages were identified that infected potato landraces (Garry et al, 2005;Vargas et al, 2009) and, as in Ecuador, the domi-nant lineage was EC-1. Some studies on P. infestans populations indicated a low genetic diversity, represented by a single dominant clonal lineage but with high virulence diversity Guo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in commercial varieties and selected clones from INIAP's national potato breeding programme, 27, 17 and 37 races were found in Carchi, Cotopaxi and Pichincha provinces, respectively (Tello, 2008). In Peru and Colombia three clonal lineages were identified that infected potato landraces (Garry et al, 2005;Vargas et al, 2009) and, as in Ecuador, the domi-nant lineage was EC-1. Some studies on P. infestans populations indicated a low genetic diversity, represented by a single dominant clonal lineage but with high virulence diversity Guo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Table S1. Solanaceous species reported as hosts of Phytophthora infestans in Peru (Junchaya, 1983;Garry et al, 2005b). Table S2.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Many studies throughout the world have indicated that P. infestans populations outside central Mexico were dominated by the ‘US‐1’ clonal lineage until the 1970s (Fry, ). The situation changed with the detection of the A2 mating type from several European countries in the early 1980s (Goodwin et al ., ; Garry et al ., ). Analysis of P. infestans populations in Europe indicated that the new population displaced the previous dominant population in only a few years and was further spread worldwide (Fry, ).…”
Section: Introductionmentioning
confidence: 97%